Perilaku Kepemimpinan Yang Efektif Model 3 Dimensi: Berorientasi Pada Tugas, Hubungan, Dan Perubahan - Ahmad Saifudin (Intizam, Jurnal Manajemen Pendidikan Islam, 2020)
Leadership behavior seems to be the basic thing that must be learned, especially for those who hold leadership and or manager roles. Although not dismissing anyone to explore it. Most of us agree that a good organization will not exist without good people. And the central role of "good people" is in the hands of the leader. In this case, as a modern leadership behavior theory, there is a three-dimensional model of leadership, namely task-oriented, relationship-oriented, and change-oriented. The influence of a three-dimensional model of leadership behavior on organizational effectiveness is one example. Ideally, if an organizational leader applies the three-dimensional model of behavior, either singly or as a whole according to their skills and competencies and is supported by the right situations and conditions, it will greatly affect organizational effectiveness. The leader will influence the behavior of his followers, directly or indirectly. And the behavior of followers, both individuals and groups will influence organizational behavior; in this case it can be seen from the work climate. If the working climate is conducive and all qualities of work life can be realized, then the outcome is organizational effectiveness.